Biomolecular corona on nanoparticles: a survey of recent literature and its implications in targeted drug delivery - Pearson, Ryan M.; Juettner, Vanessa V.; Hong, Seungpyo (Frontiers in Chemistry, 2014)
Achieving controlled cellular responses of nanoparticles (NP) is critical for the successful development and translation of NP-based drug delivery systems. However, precise control over the physicochemical and biological properties of NPs could become convoluted, diminished, or completely lost as a result of the adsorption of biomolecules to their surfaces. Characterization of the formation of the ‘biomolecular’ corona has thus received increased attention due to its impact on NP and protein structure as well as its negative effect on NP-based targeted drug delivery. This review presents a concise survey of the recent literature concerning the importance of the NP-biomolecule corona and how it can be utilized to improve the in vivo efficacy of targeted delivery systems.